BOOK REVIEW ON YANN MARTEL’S “LIFE OF PI” - T.S, Marchellina Ayu (LANTERN (Journal on English Language, Culture and Literature), 2013)
Life of Pi is a fantasy adventure novel that is written by a Canadian authorYann Martel. There are some positive messages that are in this novel, such as how to face fear, how to fight to survive, and much more. There are three purposes of this writing: to give the summary of Life of Pi novel and biography of the author; to reviewLife of Pi’s intrinsic elements, the strengths, and the weaknesses of the book; and to review the cover analysis of the novel. The result shows that from the intrinsic elements that are analyzed in this novel, the writer concludes that those elements are the strengths of this novel. On the other hand,there are some contents of the novel that is boring and being a little weaknesses of this novel.In this study the writer analyzes the front cover of the novel from the illustration picture that is shown in the cover and the title on the cover. Besides, the writer also analyzes the back cover of the novel from the synopsis that is shown in there.In brief, this novel is good for the reader who loves reading. It is because this novel not only has interesting story but also has many positive messages that become the good lesson for the people who read it.